A Study of Impact of Westernization on Annang Fattening Room Culture of Akwa Ibom State, Nigeria - Toby, Emmanuel; Toby, Imaobong (NIU Journal of Social Sciences, 2026)
Fattening room which means " Mbobo " in the Annang culture of Akwa Ibom State of Nigeria is a period of transition from adolescence to womanhood prior to marriage and childbirth. The process involves the seclusion of female adolescents for a period of three months. During this period of confinement, the female adolescent is taught how to be of good conduct and maintain good behavior with her husband and the in-law family. The fattening room was used as a beauty salon for young ladies to be educated on subjects that cover cosmetology, makeup, and fashion design. This important culture of the Annang people has been influence by westernization and has not been given adequate scholarly attention in Annang studies. This paper, therefore, is to fill these obvious gaps in Annang literature by using both primary and secondary data, such as IDI, as the source of data collection to examine the fattening room culture as an African beauty salon for the Annang girls. The study reveals that the Annang fattening room tradition is declining due to western influences like urbanization and globalization, causing youth to view it as outdated culture. The study recommends integrating the fattening room practice into western schools’ system, engaging youth in cultural events, and organizing festivals that blend traditional culture and elements to enhance youth participation in fattening room. Keywords: Annang, Culture, Fattening room, Westernization